The effects of social ties on innovation behavior and new product performance in emerging economies: evidence from Turkey. Issue 4 (7th April 2020) - Yeniaras, Volkan; Kaya, Ilker; Ashill, Nick
Abstract : Purpose: The purpose of this paper is to offer a theoretical and empirical understanding of how social ties affect innovation behavior and new product performance in Turkey, which is an emerging economy where high levels of economic and political uncertainties exist.The authors examine whether innovation behavior binds the political and business ties of the firm to new product performance. They also examine if these effects are contingent on variations in the institutional environment and market environment. Design/methodology/approach: Structural equation modeling and mediation analyses were used on a sample of 344 small- and medium-sized enterprises in Istanbul. Findings: Business ties are positively related to exploratory innovation behavior and political ties hamper such behavior. The authors also show that government support hinders firms' disruptive innovation while encouraging incremental innovation behavior. The authors further demonstrate that the positive and indirect relation of business ties to new product performance through exploratory and exploitative innovation is largely insensitive to changes in market and institutional environments. Political ties are negatively (positively) and indirectly related to new product performance through exploratory (exploitative) innovation. Practical implications: Managers should choose the form of their personal interactions (political and/or business) based on the type of innovation that is being pursued. Additionally, managers should consider both the institutional environment and the market environment as important contingencies in their decision of whether to invest resources in developing social ties to build innovation behavior. Originality/value: The authors offer a deeper perspective of how social ties in emerging economies affect new product performance by considering exploratory and exploitative innovation behavior as mediating mechanisms. These mediating effects are conditional on institutional and market environments.